A spotlight on application of microwave-assisted modifications of plant derived polymers in designing novel drug delivery systems - Girish Meravanige Basavarajappa; K M Priyanka; Prakash Goudanavar; Lakshmi G Narasimha; N. Raghavendra Naveen; Buduru Gowthami; Santosh Fattepur; Predeepkumar Narayanappa Shiroorkar; Sreeharsha Nagaraja; Mallikarjun Telsang; Veeriah Chowdary Jasthi; Pavan Kumar Pavagada Sreenivasalu (Designed Monomers and Polymers, 2023)
Polymers are a fundamental part of numerous industries and can be conjugated with many other materials and components to have a vast array of products. Biomaterials have been extensively studied for their application in pharmaceutical formulation development, tissue engineering, and biomedical areas. However, the native form of many polymers has limitations concerning microbial contamination, susceptibility, solubility, and stability. Chemical or physical modifications can overcome these limitations by tailoring the properties of polymers to meet several requirements. The polymer modifications are interdisciplinary, cutting across conventional materials, physics, biology, chemistry, medicine, and engineering limitations. Microwave irradiation has become a well-established technique for a few decades to drive and promote chemical modification reactions. This technique allows ease of temperature and power control to perform the synthesis protocols efficiently. Additionally, microwave irradiation contributes to green and sustainable chemistry. In this contribution, microwave-assisted polymer modifications were described with a special focus on their application in developing several novel dosage forms.